Design of Real-Time Hardware-in-the-Loop TV Guidance System Simulation Platform - Zhongyuan Chen; Xiaoming Liu; Wanchun Chen (International Journal of Aerospace Engineering)
This paper presents a novel design of a real-time hardware-in-the-loop (HIL) missile TV guidance system simulation platform, which consists of a development computer, a target computer, a turntable, a control cabin, and a joystick. The guidance system simulation model is created on the development computer by Simulink® and then downloaded to the target computer. Afterwards, Simulink Real-Time™ runs the model in real-time. Meanwhile, the target computer uploads the real-time simulation data back to the development computer. The hardware in the simulation loop is TV camera, encoders, control cabin, servomotors, and target simulator. In terms of hardware and software, the system has been simplified compared with the existing works. The volume of the turntable integrating the target simulator and the seeker simulator is about 0.036 cubic meters compared to the original 8 cubic meters, so it has a compact structure. The platform can perform the closed-loop control, so the simulation has high precision. Taking the TV guidance simulation as an example, in the case of target maneuvering, the final miss distance of the TV guidance missile is 0.11812 m, while the miss distance of the original system is 13 m. The trajectories obtained from the HIL and mathematical simulations substantially coincide. So the simulation results show that the proposed HIL simulation platform is effective.